Analisis Tindak Tutur Ilokusi Pada Transaksi Jual Beli Di Pusat Grosir Solo - Setyaningsih, Wiwik, Prof. Dr. Abdul Ngalim M.M (2016)
This study has two objectives. 1) To describe the type of illocutionary acts that appear in buy and sell transactions in Wholesale Center of Solo. 2) to describe the functions of illocutionary speech contained in the buy and sale transactions in Wholesale Center of Solo. This study included a descriptive qualitative research. Subject of this research that buyers and sellers conduct transactions in Wholesale Center of Solo. The object this study is illocutionary speech acts were discovered when the transaction between the seller and the buyer in Wholesale Center of Solo. Data collection techniques in this study is read and record technique. Data presentation techniques using informal techniques. The results of this study there are two things. 1) Type of illocutionary acts that appear in buy and sale transactions in Wholesale Center of Solo. a) Representative speech acts include states, recognize, report, mentions and shows, b) directive speech acts include invites, requesting, asking, begging, advise, challenge, force and gave a downbeat, c) commissive speech acts include the offer, stating ability and promise, d) expressive speech acts include thanked, criticizing, blaming, complaining and praise and declarative speech acts include declarations prohibiting speech act. 2) Illocutionary speech acts function consists of four types. a) Competitive function include requesting and begging, b) pleasant includes thanked, c) cooperate include announced and reported, and d) contrary covers scolding.